Caracterización de la migración en la dama es una trampa de Galo Galarza - Paute Torres, Jimena Noemi (2015)
Considering the importance of studying the phenomenon of migration captured through the literature, this thesis entitled "Characterization of migration in The Lady is a trap (La dama es una trampa) by Galo Galarza" talks about relevant topics around migration of sensing the situation that many compatriots go through. With the background mentioned above, this thesis has the overall objective: to analyze the main characteristics of the Ecuadorian migration to North America in The Lady is a trap by Galo Galarza. Regarding the methodology, it was used the guidelines of the scientific method, to develop a logical and coherent scheme between the parts of the investigation. Later deduction was used as a means of support in the organization of the issue from a global approach: migration, specifically the one that has occurred from Ecuador to New York and Canada. In addition, it has been necessary to resort to the historical method to know the significance of this phenomenon called migration, as well as mention the events present in the book The lady is a trap. It has also made use of the analytical method to examine deeper the studied novel. Within this analysis can be seen the migratory phenomenon, description of testimonial character and the main identifying features of the migrant subject, all present in The Lady is a trap by Galo Galarza. Finally, through the conclusions , it was demonstrated certain aspects about the book studied; then, in connection with the conclusions are the recommendations which are ideas or suggestions directed towards actors in education that are linked to the literary field.